DEVELOPMENT OF WEB-BASED INTERACTIVE LEARNING MEDIA WITH DISCOVERY LEARNING MODEL ON NUMBER PATTERN MATERIAL FOR EIGHTH GRADE STUDENT OF JUNIOR HIGH SCHOOL USING CMS (CONTENT MANAGEMENT SYSTEM) WORDPRESS - Fajar Ainnur Rokhman; Ilham Rizkianto (Universitas Negeri Yogyakarta, 2026)
This research aims to: (1) produce a web-based interactive learning media with discovery learning model on number pattern material for eighth grade student of junior high school, (2) determine the feasibility of web-based interactive learning media with discovery learning model on number pattern material based on validity, practicality, and effectiveness. This study was a research and development using ADDIE model. This research was conducted at SMP Negeri 2 Karangrejo with subjects of this research were 30 students of eighth grade student of junior high school. Data collection techniques using expert validation questionnaires to test eligibility, student response questionnaires to test practicality, and competency test to test effectiveness. This study resulted in the following aspects: (1) validity in terms of the validation results of experts with a score of 4.61 and 4.79 with good category, (2) practicality in terms of the results of the student response questionnaire with a score of 3.67 with good category, (3) the effectiveness in terms of the results of the t test shows that the average results learning to use the developed web-based interactive learning media is significantly different with the comparison value and learning completeness of students reaching 83.3%. Therefore, this web-based interactive learning media are feasible to be used in learning.Keywords: learning media; web; number pattern; discovery learning.